PERFORMANCE APPRAISAL SYSTEM DESIGN IN PT. KARYA SUNLI - Johnson Hendry; Dhita Hafizha Asri (ConCEPt - Conference on Community Engagement Project, 2022)
Performance appraisal is a systematic evaluation process of employee performance that is useful for understanding a person's ability for career growth and further skill development. Performance appraisal is a tool that is used strategically to increase the effectiveness of the organization in managing its human resources. This employee performance appraisal format is expected to be able to go hand in hand with or concurrently with the evaluation, review of company performance. The design of this performance assessment format uses the Graphic Rating Scale method. The rating scale use Likert scale, which contains an assessment using several assessment indicators, namely work skills, quality, responsibility, teamwork, attitudes and communication skills.